Brief Report: A Preference for Biological Motion Predicts a Reduction in Symptom Severity 1 Year Later in Preschoolers with Autism Spectrum Disorders - Franchini, Martina; Wood de Wilde, Hilary; Glaser, Bronwyn; Gentaz, Edouard; Eliez, Stephan; Schaer, Marie (Frontiers in Psychiatry, 2016)
Recent research has consistently demonstrated reduced orienting to social stimuli in samples of young children with Autism Spectrum Disorders (ASD). However, social orienting greatly varies between individual children on the spectrum. Better understanding this heterogeneity in social orienting may contribute to our comprehension of the mechanisms underlying autistic symptoms thereby improving our ability to intervene. Indeed, children on the autism spectrum who show higher levels of interest in social stimuli demonstrate reduced clinical symptoms and increased adaptive functioning. However, longitudinal studies examining the influence of social orienting on subsequent outcome are critically lacking. Here, we aim to explore the relationship between social interest at the age of 3 and changes in severity of autistic symptoms over the subsequent year, in 20 children with ASD and 20 age-matched typically developing (TD) children. A visual preference for social stmuli was measured using an eye-tracking task at baseline, consisting of a previously studied visual preference paradigm presenting biological and geometric motion side-by-side. The task was altered for the current study by alternating presentation side for each type of stimuli to keep visual perseveration from influencing participants’ first fixation location. Clinical data were collected both at baseline and one year later at follow-up. As a group, we observed reduced interest for biological motion in children with ASD compared to TD children, corroborating previous findings. We also confirmed that a preference for biological motion is associated with better adaptive functioning in preschoolers with ASD. Most importantly, our longitudinal results showed that a preference for biological motion strongly predicted decreased severity of diagnostic symptoms. Participants who preferred social stimuli at the age of 3 showed drastic reductions in their severity level of autistic symptoms one year later, whereas participants who preferred geometric stimuli showed autistic symptoms that were unchanged or more severe after one year. As a whole, our results suggest that a preference for biological motion may be key to understanding the behavioral phenotype of young children with ASD, and may represent a promising candidate behavior for predicting early developmental trajectories and outcome.